Isolation of Mycobacterium avium and other nontuberculous mycobacteria in chickens and captive birds in Peninsular Malaysia - Abdul Sattar; Zakaria, Zunita; Abu, Jalila; A. Aziz, Saleha; Rojas-Ponce, Gabriel (BioMed Central, 2021)
Background: Mycobacterium avium complex (MAC) causes a chronic infectious in the birds known as avian mycobacteriosis. Almost all species of the birds are susceptible to MAC which consists of two closely related species of mycobacteria, that is, M. avium and M. intracellulare. This study aimed to determine the occurrence of Mycobacterium avium subsp. avium (MAA) in chickens and captive birds in selected states of Peninsular Malaysia. Results: A 300 fecal samples were collected from village chickens (n = 100), layer chickens (n = 100) and captive birds (n = 100). Fecal samples were split into two aliquots for microbiological and molecular detection of MAA. Microbiology detection consisted of microscopy (Ziehl-Neelsen staining) and culture of samples decontaminated with 1% Cetylperidinium chloride and vancomycin, nalidixic acid and amphotericin B (VNA) antibiotic cocktail [vancomycin (VAN) 100 μg/ml, nalidixic acid (NAL) 100 μg/ml and amphotericin B (AMB) 50 μg/ml] onto Löwenstein-Jensen (L-J). Molecular detection (PCR-IS901) was performed to detect MAA DNA from the feces and PCR-16S rRNA and IS901 for identification of genus Mycobacterium and Mycobacterium avium sub species avium isolated onto L-J. All samples (296) were AFB negative smear. M. avium was isolated in 0.3% (1/296) samples by culture and detected in 2.5% (6/242) samples by PCR (IS901). Other mycobacteria were found in 1.7% (5/296) chickens. Of five isolates, two were identified as Mycobacterium terrae and M. engbaekii and remaining isolates were not sequenced. Birds positive for M. avium included White Pelican (n = 1) Black Hornbill (n = 1), Macaw (n = 2), Cockatoo (n = 2) and village chicken (n = 1). Conclusion: It is concluded that chickens and birds were infected with M. avium in selected areas of Peninsular Malaysia. Although, PCR is rapid, reliable and cost effective method for detection of M. avium in a subclinical stage, the culture of the avian feces should still be used as a reference test for the diagnosis of avian tuberculosis.